ANALISIS KOMPETENSI LITERASI BACA TULIS KELAS 1 SDN BLABAK 1 - Herlina Putri, Sherly; Icha Hartanti, Levina; Laila, Alfi; Huliyyatul Maula, Saila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low literacy skills of early elementary school students, which remains a problem in the learning process. Reading and writing skills are an important foundation in supporting student learning success at the next level. This study aims to analyze the literacy skills of first-grade students at SDN Blabak 1 and identify obstacles experienced by students in the literacy learning process. The study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, initial reading and writing tests, teacher interviews, and documentation. The research subjects consisted of 14 first-grade students of SDN Blabak 1. The results showed that most students had literacy skills in the